Awareness of the risk factors for heart attack among the general public in Pahang, Malaysia: a cross-sectional study - Ahmed, Abdullah Abdulmajid Abdo; Al-Shami, Abdulkareem Mohammed; Jamshed, Shazia Qasim; Mohammed, ZAWIAH; Elnaem, Mohamed Hassan Abdelaziz; Ibrahim, Mohamad Izham Mohamad (DovePress, 2020)
Background: Cardiovascular disease is a leading nationwide cause of morbidity and mortality. Public awareness of risk factors for heart attacks is thought to impact the burden of disease, prevention, and timely management. The objective of this study was to assess the awareness of risk factors for heart attack and to identify the factors associated with the awareness of all modifiable risk factors for heart attack in the general population. Methods: This is a cross-sectional study conducted among 393 adult individuals in Kuantan, Pahang, Malaysia. Data collection was conducted through face-to-face interviews among the lay public members who were 18– 64 years old, excluding healthcare professionals in clinical settings and academic settings. Statistical analysis was performed using chi-square test and logistic regression analysis. Results: The majority of the individuals identified smoking as a risk factor for heart attack, followed by atrial fibrillation (57.7%), heart disease (54.1%), and obesity (53.8%). However, diabetes (26%) was the risk factor that was least recognized by the participants. A total of 90.6% of participants identified at least one risk factor for heart attack, while 9.8% of the participants did not identify any risk factors for heart attack, whereas 5.6% identified all modifiable heart attack risk factors. Furthermore, participants aged 46– 64 years old, married respondents, and Chinese participants, those with higher educational levels, and received prior information demonstrated great awareness of eight modifiable risk factors for heart attack. Multivariable logistic regression presented that participants with aged 55– 64, those with family history of heart attack and individuals with dyslipidemia were factors independently related to excellent awareness (p=0.04, OR=6.21, 95% CL= 1.081– 35.641), (p=0.049, OR=2.11, 95% CL=0.721– 6.230) and (p=0.009, OR= 4.08, 95% CL= 1.427– 11.685), respectively. Conclusion: Awareness of risk factors for heart attack appears to be poor, where most of the respondents recognized only one modifiable risk factor. According to these findings, programs and strategies to raise awareness of modifiable risk factors for HA are urgently needed to protect the lay public from HA.